2018
DOI: 10.1016/j.omtm.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of AAV Retrograde Pancreatic Ductal Gene Delivery in Normal and Pancreatic Cancer Mice

Abstract: Recombinant adeno-associated virus (rAAV)-mediated gene delivery shows promise to transduce the pancreas, but safety/efficacy in a neoplastic context is not well established. To identify an ideal AAV serotype, route, and vector dose and assess safety, we have investigated the use of three AAV serotypes (6, 8, and 9) expressing GFP in a self-complementary (sc) AAV vector under an EF1α promoter (scAAV.GFP) following systemic or retrograde pancreatic intraductal delivery. Systemic delivery of scAAV9.GFP transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 93 publications
2
17
0
Order By: Relevance
“…Our study shows that AAV-9-mediated miR-155 delivery was efficient in the pancreas, and the expression of the target gene TAB2 was visibly regulated. Among AAV serotypes, AAV-9 showed more efficient pancreatic delivery in vivo, mediating long-term transgene expression with no immune response 35,36 . Thus, we compared the effect of miR-155 in the cerulein AP model with that in the cerulein plus LPS or L-arginine model.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that AAV-9-mediated miR-155 delivery was efficient in the pancreas, and the expression of the target gene TAB2 was visibly regulated. Among AAV serotypes, AAV-9 showed more efficient pancreatic delivery in vivo, mediating long-term transgene expression with no immune response 35,36 . Thus, we compared the effect of miR-155 in the cerulein AP model with that in the cerulein plus LPS or L-arginine model.…”
Section: Discussionmentioning
confidence: 99%
“…Although the novel vectors described in this study mainly transduced the liver when delivered systemically, they could possibly be safely delivered in close proximity to islets using endoscopic retrograde cholangio-pancreatography (ERCP), a procedure that is routinely used in patients to examine the pancreatic and bile ducts (Hibberts & Barnes, 2003). Several recent studies have reported retrograde pancreatic intraductal delivery for safe and effective administration of rAAV vectors into the pancreas of mice (Jimenez et al, 2011;Mallol et al, 2017;Quirin et al, 2018). The vectors generated in our study could be used for gene therapy of diabetes by delivering transcription factors or small hairpin RNAs (shRNA) into pancreatic islet cells.…”
Section: Discussionmentioning
confidence: 96%
“…For in vivo gene editing, AAVs are currently the leading candidates for virus-based gene manipulation because of their broad tissue tropism, non-pathogenic nature, and low immunogenicity [30]. Although AAV6 exhibited high pancreatic tropism [31], we applied AAV2 for in vivo CRISPR delivery to establish animal model for early stage neoplasia development.…”
Section: Discussionmentioning
confidence: 99%